Looks for boolean expressions involving boolean constants and simplifies them to use the appropriate boolean expression directly.

Examples:

 Initial expression Result if (b == true) if (b) if (b == false) if (!b) if (b && true) if (b) if (b && false) if (false) if (b || true) if (true) if (b || false) if (b) e ? true : false e e ? false : true !e if (true) t(); else f(); t(); if (false) t(); else f(); f(); if (e) return true; else return false; return e; if (e) return false; else return true; return !e; if (e) b = true; else b = false; b = e; if (e) b = false; else b = true; b = !e; if (e) return true; return false; return e; if (e) return false; return true; return !e;
The resulting expression e is modified as follows:
1. Unnecessary parentheses around the expression are removed.
2. Negated applications of ! are eliminated.
3. Negated applications of comparison operators are changed to use the opposite condition.
4. Implicit conversions of pointers, including pointers to members, to bool are replaced with explicit comparisons to nullptr in C++11 or NULL in C++98/03.
5. Implicit casts to bool are replaced with explicit casts to bool.
6. Object expressions with explicit operator bool conversion operators are replaced with explicit casts to bool.
7. Implicit conversions of integral types to bool are replaced with explicit comparisons to 0.
Examples:
1. The ternary assignment bool b = (i < 0) ? true : false; has redundant parentheses and becomes bool b = i < 0;.

2. The conditional return if (!b) return false; return true; has an implied double negation and becomes return b;.

3. The conditional return if (i < 0) return false; return true; becomes return i >= 0;.

The conditional return if (i != 0) return false; return true; becomes return i == 0;.

4. The conditional return if (p) return true; return false; has an implicit conversion of a pointer to bool and becomes return p != nullptr;.

The ternary assignment bool b = (i & 1) ? true : false; has an implicit conversion of i & 1 to bool and becomes bool b = (i & 1) != 0;.

5. The conditional return if (i & 1) return true; else return false; has an implicit conversion of an integer quantity i & 1 to bool and becomes return (i & 1) != 0;

6. Given struct X { explicit operator bool(); };, and an instance x of struct X, the conditional return if (x) return true; return false; becomes return static_cast<bool>(x);

Options¶

ChainedConditionalReturn

If non-zero, conditional boolean return statements at the end of an if/else if chain will be transformed. Default is 0.

ChainedConditionalAssignment

If non-zero, conditional boolean assignments at the end of an if/else if chain will be transformed. Default is 0.